A checklist of macronyssid species (Mesostigmata: Macronyssidae) from Brazil - Bassini-Silva, Ricardo (2021)
Macronyssid mites are parasites of reptiles, birds, and mammals. A checklist of macronyssid species of Brazil is provided, containing 13 genera and 26 species collected from 99 host species.